Fetal varicella syndrome: a diagnostic dilemma. (18th April 2012) - Ballal, S; McCormack, J
Abstract : Introduction: Primary varicella zoster virus (VZV) infection is common childhood disease. Over 90% of the antenatal population in the UK are seropositive for VZV. For this reason primary VZV infection is uncommon; with an estimate of 3/1000 pregnancies. Case report: 36 years old G3 P0 presented at 12/40 weeks with history of maculopapular rash and a history of exposure to chicken pox. Her bloods confirmed the clinical diagnosis of VZV infection as her booking VZV IgG was negative. She was given 5 days of Acyclovir. At 15/40 weeks she was reviewed at the fetal services and a scan revealed an active single fetus with obvious abnormalities of both upper limbs in the form of flexion deformities and bone hypoplasia. She was counselled about possible diagnosis of fetal varicella syndrome (FVS) but informed that skeletal dysplasia could not be excluded. The patient opted to have the pregnancy terminated after a discussion of possible long term abnormalities like developmental delay associated with FVS. The post mortem showed no histological evidence of viral inclusion bodies in fetal tissue, the placenta showed possible viral inclusion bodies in deciduas but the overall findings were not typical of FVS Conclusion: Diagnostic exclusion of FVS was difficult but confirmation of a definitive skeletal dysplasia would have altered counselling and might have altered her decision to terminate the pregnancy.